Adolescent mice exposed to TBI developed PD-like pathology in middle age - Rong Sha; Mingzhe Wu; Pengfei Wang; Ziyuan Chen; Wei Lei; Shimiao Wang; Shun Gong; Guobiao Liang; Rui Zhao; Yingqun Tao (Translational Psychiatry)
Abstract Traumatic brain injury (TBI) is identified as a risk factor for Parkinson’s disease (PD), which is a neurodegenerative disease characterized by the loss of dopaminergic neurons in the substantia nigra (SN). However, the precise mechanism by which chronic TBI initiates PD pathogenesis is not yet fully understood. In our present study, we assessed the chronic progression and pathogenesis of PD-like behavior at different intervals in TBI mice. More than half of the mice exhibited PD-like behavior at 6 months post injury. PD-like behavioral dysfunction and pathological changes were aggravated with the injured time extension in chronic phase of TBI. The loss of tyrosine hydroxylase positive (TH+) neurons in the SN were partly associated with the accumulation of misfolded a-Synuclein and the cytoplasmic translocation of TDP-43 from nuclear. Moreover, the present of chronic inflammation was observed in SN of TBI mice, as evidenced by the enhancement of proinflammatory cytokines and reactive astrocytes and microgliosis post lesion. The enhanced phagocytosis of reactive microglia accounted for the reduction of dendrite spines. Our results revealed that chronic inflammation associated with the damage of TH+ neurons and the development of progressive PD-like pathology after chronic TBI in mice. Our study shed new light on the TBI-triggered molecular events on PD-like pathology. Additional research is required to have a deeper understanding of the molecular factors underlying the impairment of dopaminergic neurons following TBI.